PENGARUH ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) TERHADAP KINERJA KEUANGAN DAN REPUTASI PERUSAHAAN - Ratna Sari; Evrina Evrina; Marwan Setiawan (CV. Lafadz Jaya, 2026)
Using a literature review methodology, this study attempts to examine the effects of Environmental, Social, and Governance (ESG) adoption on business financial performance and reputation. Because ESG is thought to be able to generate long-term value and boost stakeholder trust, it is becoming a significant concern in contemporary business operations. This study's methodology is a literature review, which involves examining a variety of academic publications, research papers, and journals that are pertinent to the subjects of corporate reputation, financial performance, and ESG. According to the study's findings, implementing ESG practices often improves a company's financial performance by increasing profitability, operational effectiveness, and long-term stability. In addition, ESG practices also play an important role in building a better corporate reputation in the eyes of investors, consumers, and the wider community. However, some literature also reveals variations in results depending on the industrial sector, level of implementation, and prevailing economic and regulatory conditions. Thus, ESG is not only a tool for compliance, but also a business strategy that can increase corporate competitiveness sustainably.